2010
DOI: 10.1253/circj.cj-09-0748
|View full text |Cite
|
Sign up to set email alerts
|

Complete Elimination of Cardiodepressant IgG3 Autoantibodies by Immunoadsorption in Patients With Severe Heart Failure

Abstract: Background: Cardiodepressant IgG3 autoantibodies (CD-Abs) can be targeted by apheresis. Using blinded measurements of CD-Abs before and after immunoadsorption (IA), the cardiac function of patients who did or did not achieve complete CD-Abs elimination was compared. Methods and Results:Autoantibodies were completely removed from 18 patients with heart failure (New York Heart Assocation class 3 or 4, left ventricular ejection fraction (LVEF) <30%) using a selective IgG3 adsorption column. All patients had anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 21 publications
(11 reference statements)
1
26
0
Order By: Relevance
“…Whereas the thinning of the left ventricle wall, a common finding in DCM patients, was not observed in this model, echocardiograms showed contractile dysfunction along with chamber dilatation, which may represent an early stage of DCM. It has been unclear whether the production of autoantibodies against M 2 R in DCM patients is a result of inflammatory responses or whether such antibodies are pathogenic and actively participate in the disease progression [26][27][28][29]. Our present findings strongly suggest that the anti-M 2 R antibodies participate in the electrical remodeling of left ventricular muscles and subsequently lead to DCM-like cardiac dysfunction.…”
mentioning
confidence: 58%
“…Whereas the thinning of the left ventricle wall, a common finding in DCM patients, was not observed in this model, echocardiograms showed contractile dysfunction along with chamber dilatation, which may represent an early stage of DCM. It has been unclear whether the production of autoantibodies against M 2 R in DCM patients is a result of inflammatory responses or whether such antibodies are pathogenic and actively participate in the disease progression [26][27][28][29]. Our present findings strongly suggest that the anti-M 2 R antibodies participate in the electrical remodeling of left ventricular muscles and subsequently lead to DCM-like cardiac dysfunction.…”
mentioning
confidence: 58%
“…Often referred to as “cardio-depressant" AAbs, certain types of AAb purified from patients with DCM have been found to induce a negative inotropy in vitro (32) and ex vivo (27,33). Interestingly, patients with cardio-depressant AAbs demonstrated an acute increase in cardiac index and LVEF after IA therapy (27,32). Staudt and colleagues have reported that the cardio-depressant effects of these AAbs are unlikely to be induced by either the F(ab′) 2 or Fc fragment alone (34).…”
Section: Discussionmentioning
confidence: 99%
“…A therapeutic benefit also holds true for Immunsorba TR selective IgG3 columns, as recently investigated even under blinded measurement conditions. 11 Our previously selected aptamer using the Monolex technology 12 bound β1-AABs isolated from patients with DCM, Chagas' cardiomyopathy, or peripartum cardiomyopathy and neutralized their pathogenic functions, which we demonstrated in vitro by reducing β1-AAB-induced chronotropy and apoptosis. 1 However, as recently discussed, 13 the relationship between the selected aptamer and β1-AABs must be consolidated in vivo using animal models.…”
mentioning
confidence: 85%